The impact of isosmotic conditions on the metabolism and hypoxia tolerance of a reportedly oxyconforming teleost - Timothy D. Clark; Luis L. Kuchenmüller; Elizabeth C. Hoots; Maryane Gradito; Jake M. Martin (Journal of Fish Biology, 2026)
Fish must manage the competing demands of ion balance and gas exchange across the gills – a physiological tension known as the osmorespiratory compromise. In dynamic estuarine environments, the osmorespiratory compromise may be exacerbated by variable salinity and periods of hypoxia that demand high respiratory work. This study examined whether acute exposure to isosmotic conditions (9 ppt) lowers aerobic metabolism and enhances hypoxia tolerance relative to fresh water (0 ppt) in the fish Galaxias maculatus , a species that purportedly lacks oxyregulatory capacity when faced with hypoxia. Analysis via Bayesian mixed models found no impact of salinity on routine or standard oxygen uptake rates ( Ṁ O 2 ). The majority of fish maintained their Ṁ O 2 as oxygen declined to ~10% air saturation, with only 8 of 58 individuals displaying a measurable critical oxygen saturation (O 2crit ). Average O 2crit values were similar across treatments (25.3% in 0 ppt versus 24.3% in 9 ppt), though the small number of fish showing a clear threshold suggests that the average O 2crit of the species might be substantially lower. Contrary to earlier reports, our findings show that G. maculatus has an oxyregulatory capacity that aligns with other teleosts. The marked interindividual variability in Ṁ O 2 patterns with progressive hypoxia was a feature of this study when compared with other species, adding to a growing pattern of impressive physiological plasticity in G. maculatus . A clearer understanding of the consequences of the osmorespiratory compromise at the whole‐animal level relies on further examinations of the interplay between salinity and oxygen across stenohaline and euryhaline species and across acute and chronic exposures.

Double trouble: host behaviour influences and is influenced by co-infection with parasites - Maryane Gradito; Frédérique Dubois; Daniel W.A. Noble; Sandra A. Binning (Animal Behaviour, 2024)